1999
DOI: 10.1111/j.1600-0536.1999.tb06154.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on sensitizers in a standard patch test series

Abstract: On behalf of the European Society of Contact DermatitisPatch testing is the predominant method of establishing contact allergy. The present patch test technique is the result of a continuous process of development and improvement since its first application in the late 19th century. The perfect patch test should give no false-positive and no false-negative reactions. The ideal patch test should also cause as few adverse reactions as possible, particularly no patch test sensitization. Even though the history an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
256
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(268 citation statements)
references
References 51 publications
6
256
2
4
Order By: Relevance
“…This test has to be carried out by a dermatologist who needs all the relevant ingredients as single substances or adequate mixtures. At least substances from the European baseline patch test series [14][15][16] should be tested, and they contain different fragrance mixes as well as preservatives and other relevant substances. Preferably the product as is could be included in the test.…”
Section: Discussionmentioning
confidence: 99%
“…This test has to be carried out by a dermatologist who needs all the relevant ingredients as single substances or adequate mixtures. At least substances from the European baseline patch test series [14][15][16] should be tested, and they contain different fragrance mixes as well as preservatives and other relevant substances. Preferably the product as is could be included in the test.…”
Section: Discussionmentioning
confidence: 99%
“…The patch test is considered to be indicative for a delayed type contact allergy which requires a previous exposition to the allergen [8][9][10]. For two patients, additionally a prick test was conducted because the reaction occurred within a very short period of time after the exposure, being indicative for an immediate type (type I) of allergy, for which the prick test would be adequate for verification [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an allergen should be included in the standard series when > 0.5-1% of routinely tested patients react positively. 5 There are, however, other important factors to consider, such as the relevance of these positive reactions and certain allergens, where missing a positive patch test reaction to a certain allergen would be detrimental to treatment; such as those used in medicament creams. It is, therefore, understandable that the baseline series will vary across centres, reflecting regional differences in allergen exposures and the threshold chosen for testing.…”
Section: Introductionmentioning
confidence: 99%